"Your career will be over"—Power and contradictions in the work of educational evaluators. (June 2015) - Atjonen, Päivi
Highlights: Experiences of power and contradictions were clearly present in all evaluators' work. Power and contradictions made evaluation processes as challenging. Most challenging situations concerned evaluator's competence and methods. Also interest tensions among stakeholders or evaluated organisations existed. Sometimes power and contradictions opened new perspectives to results and their use. Abstract: The aim of this research was to study professional evaluators' experiences of power relations and contradictory issues in the evaluation processes. Utterances concerning power and contradictions were extracted by close reading of the transcribed interviews of 15 Finnish experienced evaluators. The evaluators described contradictions in the evaluator's role, in the reduced perspective of interest groups and in the cross-draughts of methodical choices. They articulated the tensions caused by personal relations, weak knowledge of criteria, focus of reporting, and the use of evaluation results. Evaluators talked about power as the use of expertise, as interactive relations, as a fight for positions, as a reporting responsibility, and as knowledge management.